Biogeographical revision of Argentina (Andean and Neotropical Regions): an analysis using freshwater fishes - López, Hugo (2008)
Aim. To provide an objective geographic framework displaying the distribution patterns of freshwater fishes from Argentina. Location. Argentina, southern South America. Methods. Parsimony analysis of endemicity (PAE) and similarity and cluster analyses were applied to presence and absence data on 440 fish species from 52 localities in Argentina. Both 50% majority consensus and strict consensus analyses were undertaken in the first case, and the Jaccard similarity index was used in the second. Results. Five ichthyogeographic provinces are described based on a PAE of the 52 localities. A cluster analysis provided similar results. Main conclusions. The following zoogeographic provinces are proposed for Argentine freshwater fish fauna following the International Code of Area Nomenclature: Andean Cuyan, Patagonian, Aymaran, Great Rivers and Pampean. The former two are placed within the Andean Subregion of the Austral Region, and the latter three within the Neotropical Subregion of the Holotropical Region. These provinces, based on results coinciding with PAE and cluster analysis, represent the first classification of Argentine provinces based on objective methods. Some small regions of endemism and some localities remain separated from the proposed regions. The new scheme includes valuable empirical information from previous schemes, and is in agreement with ecological zones and other environmental arrangements proposed earlier.